LANGUAGE AND LITERATURE - Teshaboyeva Nafisa Zubaydulla qizi,; Xalilova Sevinch, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation:  This  article  discusses  recent  reforms  in  Uzbekistan  and  their influence  on  the  development  of  language  and  literature.  It  explains  how  new educational  programs,  modern  literary  museums,  and  improved  research  centers support the study of the Uzbek language and honor the country’s great writers. The article also highlights efforts to preserve classical manuscripts, promote translation projects, and strengthen linguistic research. Overall, it shows how current reforms help Uzbekistan protect its literary heritage while encouraging modern growth and cultural development.